2020
DOI: 10.3329/jemc.v10i1.45062
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern of Antimicrobials in Urinary Tract Infection at Outpatient Department in a Tertiary Care Hospital in Dhaka

Abstract: Background: Urinary tract infection (UTI) is the most common illness affecting both males and females in almost all age groups. Hence, continuous analysis of prescribing pattern in UTI is vital. Objective: The study was designed to determine the prescribing pattern of antibiotics in UTI patients at a tertiary care hospital. Materials and Methods: A prospective observational study was carried out on 180 patients in Dhaka National Medical College Hospital from January to March 2012 by collecting data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…In Gynae & obstetrics OPD, the most commonly prescribed antibiotics were quinolones as well as other groups of antibiotics which were 23(46.0%) cases and 27(54.0%) cases respectively. In our research it was found that cephalosporin accounted 31.78% of total antibiotic prescriptions which is high as compared to the study conducted in Nepal and Turkey but low than India [9][10][11] . The highest uses were by cefixime, cefuroxime and ceftriaxone for respiratory infections and other infections.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In Gynae & obstetrics OPD, the most commonly prescribed antibiotics were quinolones as well as other groups of antibiotics which were 23(46.0%) cases and 27(54.0%) cases respectively. In our research it was found that cephalosporin accounted 31.78% of total antibiotic prescriptions which is high as compared to the study conducted in Nepal and Turkey but low than India [9][10][11] . The highest uses were by cefixime, cefuroxime and ceftriaxone for respiratory infections and other infections.…”
Section: Discussioncontrasting
confidence: 46%
“…The most commonly prescribed antibiotics at medicine OPD was Cephalosporin which was 19(51.4%) cases followed by others antibiotics and azithromycin which was 9(24.3%) cases and 8(21.6%) cases respectively. In surgery OPD, the most commonly used antibiotics were flucloxacillin and cephalosporin which was 66(82.5%) cases and 24(30.0%) cases respectively 9 . In Gynae & obstetrics OPD, the most commonly prescribed antibiotics were quinolones as well as other groups of antibiotics which were 23(46.0%) cases and 27(54.0%) cases respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prescription may be handwritten on printed prescription forms that are assembled into pads or printed onto similar forms using a computer printer. In some cases, a prescription may be transmitted from the physician to the pharmacist verbally by telephone, although this practice may increase the risk of medical error 6 . The content of the prescription includes the name and address of the prescribing provider and any other legal requirement such as registration number.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Culture sensitivity tests were also important in case of UTI to go for a specific antibiotic treatment rather than the empirical treatment for the patients. 15,16 Ideally, the antimicrobial agent chosen should be well tolerated, well absorbed, achieve high urinary concentrations, and have a spectrum of activity limited to the known or suspected pathogen(s). 17,18 Bacterial strains, even from the same species, may vary widely in sensitivity to antibiotics.…”
Section: Introductionmentioning
confidence: 99%